Something for everyone? The different approaches of academic disciplines to Open Educational Resources and the impact on widening participation - Tony Coughlan; Leigh-Anne Perryman (Flexible Learning Association of New Zealand, 2011)
This article explores the relationship between academic disciplines' representation in the United Kingdom Open University's (OU) OpenLearn open educational resources (OER) repository and in the OU's fee-paying curriculum. Becher's (1989) typology was used to subdivide the OpenLearn and OU fee-paying curriculum content into four disciplinary categories: Hard Pure (e.g., Science), Hard Applied (e.g., Technology), Soft Pure (e.g., Arts) and Soft Applied (e.g., Education). It was found that while Hard Pure and Hard Applied disciplines enjoy an increased share of the OER curriculum, Soft Applied disciplines are under-represented as OER. Possible reasons for this disparity are proposed and Becher's typology is adapted to be more appropriate to 21st-century higher education.